1996
DOI: 10.1111/j.1365-294x.1996.tb00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Founder effects and sex ratio in the gynodioecious Thymus vulgaris L.

Abstract: Thymus vulgaris is a gynodioecious species (in which females and hermaphrodites coexist) with a highly variable frequency of females among natural populations (5–95%) and a high average female frequency (60%). Sex determination involves both cytoplasmic genes responsible for male sterility, i.e. the female phenotype, and specific nuclear factors responsible for the restoration of male fertility, and thus a hermaphrodite phenotype. In this study, molecular markers of the mitochondrial genome have been used to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 40 publications
(16 reference statements)
3
64
0
Order By: Relevance
“…Gynodioecy determined by the nuclear-cytoplasmic inheritance often has a large variation in sex ratio among populations (Manicacci et al 1996;Delph & Carroll 2001), whereas gynodioecious populations determined by nuclear inheritance have a stable sex ratio and the frequency of female plants might not exceed 50% (Bailey & Delph 2007;Spigler & Ashman 2012). Small variation in sex ratio among populations and over years suggests that gynodioecy in D. jezoensis is determined by the nuclear inheritance system.…”
Section: Sex Ratio and Sexual Labilitymentioning
confidence: 96%
“…Gynodioecy determined by the nuclear-cytoplasmic inheritance often has a large variation in sex ratio among populations (Manicacci et al 1996;Delph & Carroll 2001), whereas gynodioecious populations determined by nuclear inheritance have a stable sex ratio and the frequency of female plants might not exceed 50% (Bailey & Delph 2007;Spigler & Ashman 2012). Small variation in sex ratio among populations and over years suggests that gynodioecy in D. jezoensis is determined by the nuclear inheritance system.…”
Section: Sex Ratio and Sexual Labilitymentioning
confidence: 96%
“…Indeed, about 50% of trees from Brownhill Creek display haplotype 9 (referred as CCK in Besnard et al, 2000), which was shown to be strictly associated to a cytoplasmic male sterility (CMS) in cultivars (Besnard et al, 2000). This CMS may play a significant role in the dynamics of invasion since male sterile individuals are known to be very vigorous in olives (for example, cultivars Zarazi, Chemlal or Olivière; Besnard et al, 2000) and should therefore be favored in the initial establishment of populations compared to hermaphrodites as shown in Thymus vulgaris (Manicacci et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Associations between mtDNA haplotypes and sex expression have been found in natural populations of wild beets (Beta maritima, Cuguen et al 1994), plantains (P. lanceolata, De Haan et al 1997b), thyme (T. vulgaris, Belhassen et al 1993Manicacci et al 1996), and now bladder campion (S. vulgaris). Sex expression in S. vulgaris is cytonuclear (Charlesworth and Laporte 1998;Taylor et al 2001), and crossing studies using plants from the studied populations have detected the presence of multiple CMS factors that are statistically associated with different mtDNA haplotypes (Taylor et al 2001).…”
Section: Associations Between Sex Expression and Haplotypementioning
confidence: 99%
“…Theoretical investigations suggest that high frequencies of females can occur when their restorer frequencies are low (Frank 1989;Gouyon et al 1991). High frequencies of females can result from random processes such as those during founder events when a CMS type colonizes a new site and restorers are initially absent or in low frequency (Manicacci et al 1996). Population variation in sex ratio might therefore reflect the population genetic structure of genes controlling sex expression.…”
mentioning
confidence: 99%